Design and Modelling of Eco-Friendly CH3NH3SnI3-Based Perovskite Solar Cells with Suitable Transport Layers - M. Mottakin (MDPI AG, 2021)
An ideal n-i-p perovskite solar cell employing a Pb free CH3NH3SnI3 absorber layer was suggested and modelled. A comparative study for different electron transport materials has been performed for three devices keeping CuO hole transport material (HTL) constant. SCAPS-1D numerical simulator is used to quantify the effects of amphoteric defect based on CH3NH3SnI3 absorber layer and the interface characteristics of both the electron transport layer (ETL) and hole transport layer (HTL). The study demonstrates that amphoteric defects in the absorber layer impact device performance significantly more than interface defects (IDL). The cell performed best at room temperature. Due to a reduction in Voc, PCE decreases with temperature. Defect tolerance limit for IL1 is 1013 cm−3, 1016 cm−3 and 1012 cm−3 for structures 1, 2 and 3 respectively. The defect tolerance limit for IL2 is 1014 cm−3. With the proposed device structure FTO/PCBM/CH3NH3SnI3/CuO shows the maximum efficiency of 25.45% (Voc = 0.97 V, Jsc = 35.19 mA/cm2, FF = 74.38%), for the structure FTO/TiO2/CH3NH3SnI3/CuO the best PCE is obtained 26.92% (Voc = 0.99 V, Jsc = 36.81 mA/cm2, FF = 73.80%) and device structure of FTO/WO3/CH3NH3SnI3/CuO gives the maximum efficiency 24.57% (Voc = 0.90 V, Jsc = 36.73 mA/cm2, FF = 74.93%) under optimum conditions. Compared to others, the FTO/TiO2/CH3NH3SnI3/CuO system provides better performance and better defect tolerance capacity.